THE EFFECT OF THE USE OF LIQUID SMOKE WITH DIFFERENT CONCENTRATIONS ON THE QUALITY OF SKIPJACK KATSUOBUSHI (Katsuwonus pelamis) - Tohir Abdul Majid; Syahrul Syahrul; Sukirno Mus (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
abstractThis study aimed to determine the effect of the use of liquid smoke with a different concentration on skipjack tuna (Katsuwonus pelamis) katsuobushi quality. The research method used was the experimental method with a non-factorial Randomized Complete Design (CRD) design with three levels namely 5% (K1), 7% (K2) and 9% (K3A) with replications three times to obtain 9 experimental units. The data obtained first is tabulated into table form and analyzed statistically by analysis of variance (ANOVA). The results showed that K3treatment was the best organoleptic treatment (appearance, taste, texture and aroma) and proximate analysis (water, ash, protein, fat and phenol). Furthermore, the results of the total microbiological test of fungal colonies in the best treatment were 3.6 x 103colonies/g. The type of fungus that grows on all products was Aspergillus sp.Keywords: katsuobushi, liquid smoke, skipjack.